Isolation and uniplex polymerase chain reaction-based detection of Salmonella spp. in native chickens (Gallus gallus domesticus Linn.) from selected live bird markets in Batangas, Philippines - Galvez, John Paul F.; Umali, Dennis (2021)
Salmonellosis continues to be a pressing problem in poultry. Currently, data gap exists between the distribution and prevalence of Salmonella spp. in live bird markets (LBM) in the Philippines. Hence, isolation and molecular detection of Salmonella in native chickens from four LBMs in Batangas, Philippines were performed. Conventional bacterial isolation and uniplex polymerase chain reaction (PCR)-based assay were utilized for detection of Salmonella. A total of 114 samples composed of 16 pooled cloacal swabs, 49 liver samples, and 49 caecum samples were used for bacterial isolation. For PCR, 38 pooled samples were utilized which comprised of 10 pooled HTT broth from liver, 10 pooled HTT broth from cecum, and 18 pooled cloacal swabs. Results showed that 1/16 (6.25%) of the cloacal swabs and 1/114 of the total samples (0.88%) were positive for Salmonella in bacterial isolation. In comparison, uniplex PCR showed a detection rate of 12/18 (66.67%) in pooled cloacal swabs and an average positivity detection rate of 31.57%. Among the LBMs, Lemery had the highest PCR-positivity rate which is 6/15 (40%) compared to 1/8 (12.5%) for Padre Garcia and 5/15 (33.33%) for Rosario. Routine surveillance for Salmonella contamination is essential in preventing foodborne diseases from poultry in the Philippines.
Keywords: Salmonellosis; PCR; Chickens